KONSEP PENDIDIKAN ISLAM MODERN DALAM PERSPEKTIF KIAI PESANTREN: (Studi Tentang Konsep Islamisasi dan Integrasi Ilmu di Situbondo) - Kholilur Rahman (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
This paper attempts unravel construction of Kiai of Islamic Boarding thoughts on two issues are Islamic education modern, Islamization and integration of science. Election of Kiai pesantren is subject of research which intended as test case to assumption of issues in Islamic education, all this time become elite consumption on formal Islamic education on a limited basis. For research feasibility, we limit the research to Kiai leader of Pesantren in Situbondo. Situbondo was choosed by consideration, this city has religious fanaticism, including a strong religious education, many Islamic Boarding and Kiai and there are institutes of Islamic.